Massie : a Clique novel - Harrison, Lisi (Clique summer collection, 2008)
When Massie is kicked out of her exclusive riding camp and her parents insist that she get a summer job, she becomes the highest-selling Be Pretty Cosmetics girl ever by ignoring the company's philosophy.